Palladium-catalyzed C–H glycosylation and retro Diels–Alder tandem reaction via structurally modified norbornadienes (smNBDs). Issue 39 (15th September 2021) - An, Yang; Zhang, Bo-Sheng; Ding, Ya-Nan; Zhang, Zhe; Gou, Xue-Ya; Li, Xue-Song; Wang, Xiaolei; Li, Yuke; Liang, Yong-Min
Abstract : This report describes palladium-catalyzed C–H glycosylation and retro Diels–Alder tandem reaction via structurally modified norbornadienes (smNBDs). Abstract : This report describes palladium-catalyzed C–H glycosylation and retro Diels–Alder tandem reaction via structurally modified norbornadienes (smNBDs). smNBDs were proposed to regulate the reactivity of the aryl-norbornadiene-palladacycle (ANP), including its high chemoselectivity and regioselectivity, which were the key to constructing C2 and C3 unsubstituted C4-glycosidic indoles. The scope of this substrate is extensive; the halogenated six-membered and five-membered glycosides were applied to the reaction smoothly, and N -alkyl (primary, secondary and tertiary) C4-glycosidic indoles can also be obtained by this method. In terms of mechanism, the key ANP intermediates characterized by X-ray single-crystal diffraction and further controlled experiments proved that the migration-insertion of smNBDs with phenylpalladium intermediate endows them with high chemo- and regioselectivity. Finally, density functional theory (DFT) calculation further verified the rationality of the mechanism.